Effects of seepage behaviors on coal spontaneous combustion in longwall gobs: an investigation between Darcy and non-Darcy seepage. (15th August 2022) - Liu, Wei; Zhou, Yujun; Chu, Xiangyu; Qin, Yueping; Hu, Junfeng
Highlights: Seepage behavior in the broken rock is more consistent with the non-Darcy seepage; Multi-fields coupled model of the CSC under non-Darcy seepage was established; Effects of non-Darcy seepage parameters on the CSC in the longwall gob were evaluated. Abstract: Seepage behaviors of air leakage directly affect the coal spontaneous combustion (CSC) in longwall gobs, which is usually regarded as Darcy flow, but in fact, non-linear seepage should better characterize the properties of air flow in the gobs. To address this issue, steady-state percolation tests were conducted on broken rocks with five particle sizes, and the non-Darcy permeability parameters versus porosity and particle size were obtained by binary fitting the experimental data, and then applied to an actual longwall gob. The multi-physics coupling model of CSC in longwall gobs was modified accordingly, which was then validated by comparing with on-site observation data. Numerical solving procedures based on Darcy seepage and non-Darcy seepage were developed separately to quantify the effects of these two types of seepage on the CSC. The results show that (i) the seepage tests confirm that the seepage behavior in the broken rocks is more consistent with the non-Darcy seepage; (ii) the distributions of oxygen concentration and solid temperature under the two seepage flows are relatively similar, but the high-temperature zone in the gob under non-Darcy seepage is larger and hotter; (iii) the non-Darcy permeability coefficient has a positive effect on the coal temperature rise in the gob, while the non-Darcy flow factor has almost no effect, so taking plugging measures at the working face can effectively prevent the spontaneous combustion in gobs. This work contributes to the understanding of the air seepage behavior in longwall gobs and its impact on the CSC.